Impact of COVID-19 on the Income of Entrepreneurs Who Borrowed from SHG. (May 2023) - Malhotra, Nishi; Baag, Pankaj Kumar
The COVID-19 pandemic has shaken the world. After liberalization in 1991, microfinance became a panacea for poor people without collateral and information asymmetry. The higher cost of microfinance and debt traps highlighted the need for the state to intervene in resource redistribution. In addition, national lockdowns and COVID-19 restrictions have made it difficult for emerging economies like India to achieve this sustainable development goal. The Reserve Bank of India introduced self-help group (SHG) bank linkage to ensure the financial inclusion of the poor. The difference-in-difference method examined how SHGs affect entrepreneur households' income. CMIE Consumer Pyramid dx data were used for analysis. The data establish that SHGs have increased the income of the households, and demographic factors such as education, income level and gender also impact the financial inclusion of the poor.